Aktivitas Penyembuhan Luka Infeksi Krim Kombinasi Daun Sirsak (Annona muricata L.) Dan Daun Sirih (Piper betle L.) Dengan Bakteri Staphylococcus aureus Pada Punggung Kelinci New Zealand White Secara In Vivo - Indah Ana Resti; Dwi Ningsih (Faculty of Pharmacy, Universitas Muslim Indonesia, 2022)
Several types of tropical plants in Indonesia that contain anti-bacterial chemical compounds such as tannins, flavonoids and saponins, namely betel (Piper betle L.) leaves and soursop (Annona muricata L.) leaves. Objectives of the research was to determine activity of cream from soursop (Annona muricata L.) leaves ethanol extract and betel (Piper betle L.) leaves ethanol extract on the backs of rabbits infected with Staphylococcus aureus bacteria. In addition, the research conducted could also determine the stability of cream that produced and its pharmacological effects. Data analysis technique using ANOVA method, significance value did not reach 0.05. Extraction process using 70% ethanol as solvent with extraction method, namely maceration. Parameters of cream preparation were from level of storage duration for 0 days and concentration used. Then the level of cream preparation effectiveness in wounds healing could be seen from observations of wounds and pus drying time as well as edema and erythema loss. Cream preparation from combination of soursop (Annona muricata L.) leaves ethanol extract and betel (Piper betle L.) ethanol extract in formula 6 with concentration ratio of 10%: 12.5%, resulted better and faster healing rate against Staphylococcus aureus infection than other formulas. Required recovery time interval was 10 days and cream preparation had good stability.